Pengaruh Kualitas Akrual terhadap Keputusan Investasi dengan Kualitas Audit Multidimensi sebagai Variabel Moderasi (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2018) - Aditya Ari Rachman; Pujiono Pujiono (Universitas Muhammadiyah Enrekang, 2021)
This study aims to analyze the effect of accrual quality on investment decisions with audit quality as a moderating variable. Accrual quality is measured using the Modified Jones model. Investment decisions are measured using the window period method of the company's daily share price for the March-April period. Audit quality is measured by the Audit Quality Metric Score (AQMS) method which includes the dimensions of competence and independence. The research sample is a manufacturing sector company listed on the Indonesia Stock Exchange for the period 2014-2018, with the regression model used in this study is Moderated Regression Analysis (MRA). The results of this study prove that investment decisions are influenced by accrual quality. Investors need information on the quality of accruals to help make investment decisions. This is done in order to avoid risks when the company performs earnings management practices. The next results show that audit quality acts as a provider of accountable external information, not as a moderator for the relationship between accrual quality and investment decisions. Thus, the AQMS audit quality can be said to be a Predictor Moderator.